Risk of cancer in patients with autoimmune pancreatitis: a single-center experience from Germany - Schneider, Alexander; Hirth, Michael; Münch, Markus; Weiß, Christel; Ebert, Matthias; Pfützer, Roland (Digestion, 2017)
Background/Aims: Autoimmune pancreatitis (AIP) has been associated with an increased risk of malignant diseases. We aimed to describe the incidence of malignant diseases in patients with AIP compared to the general population and to characterize the clinical presentation of these patients. Methods: We retrospectively analyzed data from 28 patients with AIP presenting to the clinic (periods 1998 until 2010, 2012 until September 2015). We retrieved the expected cancer incidence of the general population from the German cancer registry. We determined the ratio of patients with malignant disease, characterized the clinical presentation of these patients, and calculated standardized incidence ratios (SIR). Results: We observed 6 malignant diseases in 5 patients with AIP (non-Hodgkin lymphoma, colon cancer, breast cancer and ovarian carcinoma, breast cancer, bladder cancer, n = 5/28, 17.9%) during an overall observation period of 223 person-years (2,675 months). The overall SIR of cancer in patients with AIP was 17.3 (95% CI 5.9-35.8), and the overall incidence rate of malignant diseases in these patients was significantly increased compared to the expected incidence in the German population (Fisher's exact test, p < 0.001). Conclusion: The incidence of malignant diseases in patients with AIP is significantly increased compared to the general population. Careful clinical monitoring is required in individuals with AIP to exclude the occurrence of malignancy.